The Effect of Duration of Administration and Discontinuation of Fluorometholone Eye Drops on The Trabecular Meshwork - Sandi Muslim; Arnila Novitasari Saubig; Riski Prihatningtias; A. Kentar Arimadyo Sulakso; Fifin Luthfia Rahmi (Journal of Biomedicine and Translational Research, 2022)
Background: The extracellular matrix (ECM) in the trabecular meshwork (TM) may play a role in the steroid-induced aqueous humor outflow resistance pathophysiology. Topical steroids such as fluorometholone can cause elevated intraocular pressure. Increased synthesis and accumulation of TM ECM proteins due to steroids result in TM dysfunction and elevated intraocular pressure.Purpose: This study aims to analyze the effect of duration of administration and discontinuation of fluorometholone eye drops on the thickness of the TM ECM of Wistar rats.Methods: This study was an experimental study with a posttest-only control group design. The total sample of 25 rats was divided into 5 groups: Treatment 1 was given topical fluorometholone for 4 weeks and stopped for 4 weeks. Treatment 2 was given fluorometholone for 6 weeks and stopped for 4 weeks. Control 1 was given topical fluorometholone for 4 weeks, Control 2 was given topical fluorometholone for 6 weeks, and the negative control was used as a baseline. TM ECM examination was assessed using histopathological score grading. This study used the Mann-Whitney test and the Kruskal-Wallis comparative hypothesis test.Results: The difference in ECM thickness was not statistically significant either between treatment group 1 and treatment group 2 (p=1.000) or control group 1 (p=0,1000). There was a significant change in the thickness of the TM ECM in treatment group 1, treatment 2, control 1, control 2 compared to the negative control (p=0.003, p=0.003, p=0.003, p=0.004).Conclusion: TM ECM thickness did not return to normal thickness after administration of fluorometholone eye drops one drop 4 times a day for 4 weeks and 6 weeks followed by discontinuation of the drug for 4 weeks. The thickness of the TM ECM was thicker in experimental rats with a longer duration of administration of fluorometholone eye drops.